Capitalism, Globalization & Islamic Economic System - Muhammad Zeeshan Farrukh (Islamic Economics Journal, 2012)
This paper explains the principles of Islamic economic system by differentiating conven-tional and Islamic economic systems. It is proved that there is an absolute clash between the secular and Islamic concept of economics as the one is self-centric while the other is based upon the welfare of the society respectively. The main reason of this attitude is the concept of akhirah (life after death) in Islamic economics but no such concept in western or secular concept, because the secular economic concept separates the religious thought from the worldly life. It is a pity fact that the present globalized world has been captured in the evil of self-centric economic system i.e. Capitalism.The main objective of Islam is to establish and maintain a welfare state which can be achieved by equitable distribution of wealth therefore Islam gives secondary importance to but the secular concept gives primary importance and wealth accumulation is the main objective of this concept.In this paper, the point of view has been explained with references from the Qura’anic verses and Ahadith. It has been explained that Islamic Economic System is not the name of implementation of just few Islamic Economic principles and modes in a society but it has linkage with the whole religion otherwise the fruits of this system could not be obtained.As far as prevalent Islamic Financial system is concerned, it is a good step towards the implementation of Islamic economic system but there is a requirement of seriousness in this context so that there is an obligation upon every Muslim to play a part to implement Islamic economic system.